A study on bacterial vaginosis in pregnancy and its effect on pregnancy outcome - Chikicherla, Sai Deepthi; Sitalakshmi, V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Bacterial vaginosis is an extremely prevalent vaginal condition and one of the causes of vaginitis among both pregnant and non pregnant women and associated with severe sequelae. Fifty percent of the women are asymptomatic. Current studies have found that the prevalence of BV ranges from 15% to 30% among non-pregnant women and 10% to 41% among pregnant women. Methods: This is a prospective study conducted among 150 pregnant women who attended the antenatal outpatient and inpatient clinic in the Department of Obstetrics and Gynaecology at Narayana Medical College and Hospital, Nellore over a period of two years from Oct 2016 to Oct 2018. Obstetric cases fulfilling the inclusion and exclusion criteria were enrolled in the study by convenient sampling technique. They were followed till the outcome of pregnancy. The data was subjected to usual statistical analysis by employing the chi-square tests. Results: Prevalence of the bacterial vaginosis was 20% in the present study. BV was significantly (p<0.05) associated with preterm delivery, PPROM, low birth weight, low APGAR and neonatal jaundice. Neonatal sepsis and congenital abnormalities showed no statistically significant difference (p>0.05) between BV positive and negative women. Conclusions: Considering the vast spectrum of maternal and fetal morbidity associated with this infection, and the availability of rapid inexpensive diagnostic tests it may be prudent to screen BV in pregnancy, so that it may be treated early and hence prevent the adverse pregnancy outcomes.